Power services scheduling algorithm based on quantum communication - Zhuozhi YU; Yefeng ZHANG; Bingyang HAN; Wenwei CHEN; Dong WANG (Dianxin kexue)
Quantum communication could effectively improve the transmission’s reliability and security of power system services.However,limited by the generating rate of quantum key,it was difficult to meet the encryption requirements of important services.Therefore,a queue scheduling algorithm was required to legitimately schedule the power system services which need to be encrypted in quantum communication.An improved weighted fair queuing (weighted fair queuing,WFQ) algorithm LD-WFQ was proposed.By estimating the expected delay of the data packets to be encrypted,sending the packets that would soon be timeout,the proposed algorithm effectively reduced the timeout ratio of the packets and improved the effective utilization of quantum keys,while maintaining the timeout ratio of the packets in high priority queue at a low level.Compared with the WFQ algorithm,the simulation result proves the superiority of LD-WFQ algorithm.